Upaya Penguatan Skill Siswa melalui Pelatihan Kewirausahaan, Akuntansi, dan Hukum Bullying - Dewi Gunherani; Sri Agustini; Muliyani Muliyani; Widiyanti Rahayu Budi Astuti; Fithrah Kamaliyah (Universitas Mathla'ul Anwar Banten, 2022)
EFFORTS TO STRENGTHEN STUDENT SKILLS THROUGH ENTREPRENEURSHIP TRAINING, ACCOUNTING, AND BULLYING LAW. The Efforts to Strengthen Student’s Skills through Entrepreneurship Training, Accounting, and Law of Bullying. graduates of SMK Mitra Bakti Husada - Bekasi majoring in Nursing and Pharmacy with the business world, because they are intended as ready-to-use personnel who are struggling to provide nursing and pharmacy services that are needed by hospitals and pharmacies for medical services to the community or can also be used as ready-made workers in drug and pharmaceutical companies that serve the community. Nursing assistants and pharmacist assistants really need to be equipped with knowledge of entrepreneurship, accounting and law. Entering the business world, like it or not, in order to be successful, it must be done professionally, which is equipped with the skills to manage finances and taxes, so that in managing finances, students need to be equipped with this knowledge. The training programs that will be provided are entrepreneurship, accounting and law. The program was chosen because it is considered important and is expected to provide education to these students. This material is an important material as a provision for them to improve their ability to be entrepreneurs, be able to manage finances and maintain social ethics, and respect each other.